COMPARISON OF CARVEDILOL AND BISOPROLOL EFFICACY IN PATIENTS WITH CHRONIC HEART FAILURE AND DIABETES TYPES 2 AFTER MYOCARDIAL INFARCTION - M. E. Statsenko; S. V. Belenkova; O. E. Sporova; D. A. Ivanova; E. D. Evtereva (Столичная издательская компания, 2016)
Aim. To compare efficacy of carvedilol and bisoprolol in patients with chronic heart failure (CHF) and diabetes mellitus (DM) type 2 after myocardial infarction (MI).Material and methods. 60 patients (45-70 y.o.) with CHF 2-3 functional class according to NYHA and DM type 2 after MI (3-4 week) are included in the study. Patients are randomized on 2 groups. All patients received basic therapy of CHF. Besides patients of 1st group (n=30) were treated with carvedilol (Talliton, Egis) 29,0±2,5 mg daily. Patients of 2nd group (n=30) were treated with bisoprolol (6,0±0,5 mg/day). Both groups were similar on age, sex, disease severity, haemodynamic parameters and basic therapy doses. Life quality, functional reserve, echocardiography, kidney function, heart rate variability (HRV), lipid and glucose metabolism were estimated initially and in 16 weeks of treatment.Results. Carvedilol and bisoprolol therapy of patients with CHF and DM after MI resulted in improvement of clinical status, kidney function and increase in HRV. Carvedilol had clinical advantages in comparison with bisoprolol in effects on myocardial remodeling, kidney function and HRV. Carvedilol favorable effects on lipid and glucose metabolism were observed.Conclusion. Carvedilol has a number of significant advantages in comparison with bisoprolol in the therapy of patients with CHF and DM after MI.